Variations of Aerosol Optical Depth in Bhaktapur, Nepal - Sharma, Niranjan Prasad (Journal of the Institute of Engineering, 2018)
The study is based on the variations of aerosol optical depth in Bhaktapur, Nepal. Microtops II Sunphotometer, manufactured by solar light inc. USA was used to measure the Aerosol optical depth. The diurnal variations of Aerosol Optical Depth (AOD) in January, 9 at 2.32UT were found to be 1.01, 0.89, 0.81 and 0.61 at 340,440, 500 and 675nm respectively. Besides ozone and clouds, aerosol plays an influencing role to attenuate solar UV radiation reaching the ground. Spectral dependence of AOD possesses higher values at shorter wavelengths and gradually decreases towards longer wavelengths in all seasons. The value of wavelength exponent (α) and aerosols concentration (β) on June 15 and July 25 at Kaushaltar were found to be 0.80, 0.56 and 0.45, 0.57 respectively. Journal of the Institute of Engineering, 2017, 13(1): 133-138